GRAMMATICAL COLLOCATION OF IMPERATIVES IN PRODUCT USER GUIDE - Erlangga, Fajar (ASIAN PUBLISHER, 2022)
This research was conducted to find out what kind of English grammatical collocation used in Imperatives in Product User Guide. The research applied a qualitative descriptive method, the data from which were collected, analyzed and concluded without drawing a general conclusion. The data of this study are grammatical collocations in imperatives found in KRISBOW Impact Drill 500W User Guide. The analysis of the 69 collected data shows there are as many as 1 type GB data (1.4%), 2 GD type data (2.9%), 12 type Gd data (17.4%), 1 type GE data (1.4%), 2 type GH data (2.9%), 1 type GI data (1.4%), 8 type GL data (11.6%), 8 type GN data (11.6%), 29 type GP data (42.02%), 3 type GQ data (4.3%), 2 type Gs data (2.9%). In conclusion, type GP (Verb + (O) + Adverbial) is the most frequently used grammatical collocation in the form of imperatives in the User Guide.